Transcranial electrical stimulation in post-traumatic stress disorder and brain injury: possibilities of tuning neuronal networks - Smashna , O.Y. (Medicni Perspektivi, 2024)
Transcranial direct current stimulation (tDCS) in the treatment of post-traumatic stress disorder (PTSD) is used to strengthen the inhibitory control of amygdala activity. However, there are still limited meta-analytic studies examining different tDCS protocols on core PTSD symptoms and the relationship between stimulation parameters and effect size. The objective is to investigate the effectiveness of such an intervention, which is a complex combination of a psychotherapy program with tDCS in the treatment of patients with PTSD and mild traumatic brain injury (mTBI) by assessing their level of functioning. 329 veterans (PTSD (n=109), mTBI (n=112), PTSD + mTBI (n=108) were examined using WHODAS 2.0. Standardized treatment was provided as well as psychotherapeutic intervention - a combination of psychoeducation with motivational interviewing and acceptance and commitment therapy for PTSD and tDCS. Clinical targets of therapy in the PTSD group were symptoms of intrusion, avoidance, hyperactivation and protocol of tDCS was dorsolateral prefrontal cortex arousing stimulation. In PTSD + TBI group clinical targets were neurocognitive symptoms, intrusion symptoms, avoidance, hyperactivation and tDCT protocol was motor cortex-supraorbital area inhibitory stimulation. The targest for TBI group was neurocognitive symptoms and tDCS protocol was occipital region exciting stimulation. The long-term effectiveness and the impact on neuroplasticity processes allow considering transcranial direct current stimulation as a promising method of neurorehabilitation of patients with a combination of posttraumatic stress disorder and mild traumatic brain injury.